Distribution system feeder re-phasing considering voltage-dependency of loads. (March 2016) - Singh, Devender; Misra, Rakesh K.; Mishra, Sujeet
Highlights: Re-phasing is sensitive to voltage-dependency of loads. Voltage improvement due to re-phasing increases the load demand. System after re-phasing may suggest more MVA margins at the main substation if appropriate load model is not considered. System can be balanced substantially in terms of phase currents, phase voltages and losses per phase using PSO. Abstract: Phase-balancing creates voltage changes in the network which calls for incorporating voltage-dependency of loads in the process of phase-balancing. Hence, inclusion of voltage-dependency in current-injection based three-phase load flow is investigated and the results are compared with constant-power load model in terms of phase-balancing. The problem being combinatorial, application of particle swarm optimization is investigated for phase-balancing problem of radial distribution network. The effects of phase unbalance and load representation are studied in terms of various parameters. It is observed that there are situations that lead to increase in losses despite improvement in phase-balancing.